Management of Osteochondritis Dissecans of the Femoral Condyle: A Critical Analysis Review. Issue 3 (March 2018) - Chan, Charles; Richmond, Connor; Shea, Kevin G.; Frick, Steven L.
Abstract : Osteochondritis dissecans of the femoral condyle remains poorly understood, with an unclear etiology. Lesions that separate have a poor prognosis, thus making treatment strategies that promote healing and prevent separation attractive. Magnetic resonance imaging is the preferred imaging modality and can predict instability well in adult patients, but with less specificity in skeletally immature patients. Classification that considers skeletally immature patients and adults differently and separates mobile from immobile lesions may be helpful in treatment decisions. A multicenter research effort is under way to address weaknesses in the current literature identified by a 2010 Clinical Practice Guideline from the American Academy of Orthopaedic Surgeons. A new arthroscopic classification system with treatment recommendations has been proposed and is being studied.